2000
DOI: 10.1007/s004250000315
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic heat-stress proteins Hsp17.7 class I and Hsp17.3 class II of tomato act as molecular chaperones in vivo

Abstract: Small heat-stress proteins (sHsps) are the most abundant stress-induced proteins with up to 20 different members in higher plants. In the cytoplasm, two different classes can be distinguished. Two cDNA clones from tomato Lycopersicon peruvianum (L.) Mill., each coding for one of the cytoplasmic sHsp subfamilies, were analyzed with respect to their transcript and protein expression, genome organization and chaperone activity. Neither type was present under control conditions but both appeared upon heat stress a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(40 citation statements)
references
References 0 publications
3
37
0
Order By: Relevance
“…For example, cluster 8, which peaked in 4-DPA pericarp, had an overrepresentation of genes in both the biotic and abiotic stress categories. These included multiple genes encoding heat-shock proteins, which may be induced by various stress responses or during development (Löw et al, 2000;Sun et al, 2002), and other proteins that are frequently induced under stress, such as MILDEW LOCUS O family proteins (Piffanelli et al, 2002) and PATHOGENESIS-RELATED proteins (Sels et al, 2008).…”
Section: Stage-dependent Expression Clustersmentioning
confidence: 99%
“…For example, cluster 8, which peaked in 4-DPA pericarp, had an overrepresentation of genes in both the biotic and abiotic stress categories. These included multiple genes encoding heat-shock proteins, which may be induced by various stress responses or during development (Löw et al, 2000;Sun et al, 2002), and other proteins that are frequently induced under stress, such as MILDEW LOCUS O family proteins (Piffanelli et al, 2002) and PATHOGENESIS-RELATED proteins (Sels et al, 2008).…”
Section: Stage-dependent Expression Clustersmentioning
confidence: 99%
“…Assembly of sHsps into cytoplasmic multichaperone complexes Formation of cytoplasmic, highly ordered multichaperone complexes consisting of sHsps as the major protein components is a characteristic feature of plant cells exposed to higher temperatures, and they are assumed to function as storage sites for heat-sensitive proteins to prevent their irreversible aggregation under hs and to keep them in a renaturation competent state for refolding by ATP-dependent chaperone machines (Forreiter et al 1997;Löw et al 2000). By immunoflorescence microscopy studies, we have shown that in addition to CI, CII, and CIII sHsps (Kirschner et al 2000;Siddique et al 2003), also members of the newly defined cytoplasmic/ nuclear sHsps CIV, CV, and CVII are recruited to HSCs upon hs (Fig.…”
Section: Regulation Of Shsp Expressionmentioning
confidence: 99%
“…The chaperone activity of CI and CII sHsps and their contribution to thermotolerance has been established in several in vivo (Forreiter et al 1997;Löw et al 2000) and in vitro studies (Lee et al 1997;Lee and Vierling 2000;Basha et al 2004) by using different heat-sensitive proteins as model substrates. In vitro, substrates denatured in the presence of CI sHsps can be refolded and reactivated by high-molecular-weight chaperones including Hsp70/DnaK, Hsp100/ClpB, and GroEL (Mogk et al 2003;Basha et al 2004;Friedrich et al 2004).…”
Section: Chaperone Activity Of Shspsmentioning
confidence: 99%
“…Ripening is marked by oxidative processes and HSP, at least chaperones, could play a role in stabilizing proteins. In tomato, small HSPs have already been shown to be involved in fruit developmental processes (Lawrence et al, 1997;Lö w et al, 2000;Neta-Sharir et al, 2005). Finally, some signature proteins can be proposed to characterize stages of development.…”
Section: Proteomic Patterns Are Associated With the Physiological Stamentioning
confidence: 99%